HUBUNGAN KEAKTIFAN IBU DALAM KUNJUNGAN POSYANDU DENGAN PERTUMBUHAN BALITA USIA 12-60 BULAN - Ulan Pratiwi Mahbubah; Herawati Mansur; ita yuliani (Poltekkes Kemenkes Malang, 2021)
Childs mortality can be reduce if the efforts to realize it from the health care of childrens. Toddler health maintenance can be done with Posyandu activities every month. Posyandu is an early detection of nutritional status of children through the growth of toddlers. Growth can be monitored well if the mother is active in Posyandu program. The activeness of the mother following the posyandu can be seen from the number of mother visits to the posyandu more than 8 times in one year listed in the KIA book. The purpose of this research is to know the correlation of mother activity in the posyandu visit with children under five growth at Posyandu RW. 10 Candirenggo Village, Singosari Sub District, Malang Regency. The population of this research a total sampling. Sample of twenty tree mothers who had KIA books and babies aged 1 until 60 months. Analytical correlation research with cross sectional approach. Data were analyzed using the Contingency Coefficient Test C. The results showed that p value equal 0, 023 less than a equal 0.05, accordingly H0 rejected, means there is relationship between mother activity visit with children under five growth 12 until 60 months in Posyandu.